2012
DOI: 10.1109/tap.2011.2167943
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Band Circularly Polarized Microstrip RFID Reader Antenna Using Metamaterial Branch-Line Coupler

Abstract: A dual-band circularly polarized aperture coupled microstrip RFID reader antenna using a metamaterial (MTM) branch-line coupler has been designed, fabricated, and measured. The proposed antenna is fabricated on a FR-4 substrate with relative permittivity of 4.6 and thickness of 1.6 mm. The MTM coupler is designed employing the provided explicit closed-form formulas. The dual-band (UHF and ISM) circularly-polarized RFID reader antenna with separate Tx and Rx ports is connected to the designed metamaterial (MTM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
94
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 13 publications
0
94
0
Order By: Relevance
“…This is especially true for the circularly polarized (CP) microstrip antenna which owns additional advantages of imposing less strict restrictions on orientation of the transmitter and receiver and mitigative multi path effects. A survey of recent literature indicates that a considerable amount of efforts have been devoted to the antennas with CP, for instance, CP antennas for bandwidth enhancement by using left handed (LH) metamaterial transmission line (TL) [8] and reactive impedance substrates [9], respectively, CP antennas with gain and directivity enhancement [10][11][12][13], omnidirectional radiations [14][15][16] and even dual-band or multifrequency operation with radiation pattern selectivity and polarization diversity [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is especially true for the circularly polarized (CP) microstrip antenna which owns additional advantages of imposing less strict restrictions on orientation of the transmitter and receiver and mitigative multi path effects. A survey of recent literature indicates that a considerable amount of efforts have been devoted to the antennas with CP, for instance, CP antennas for bandwidth enhancement by using left handed (LH) metamaterial transmission line (TL) [8] and reactive impedance substrates [9], respectively, CP antennas with gain and directivity enhancement [10][11][12][13], omnidirectional radiations [14][15][16] and even dual-band or multifrequency operation with radiation pattern selectivity and polarization diversity [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the multiband antennas [16][17][18][19][20][21][22][23][24][25] with one or more CP bands have generated much attention because the multifunctional systems exhibit the benefits of high stability, reliability and integrity. Although these antennas present a miniaturized layout at the lowest resonant mode and decent CP radiation performances with good axial ratios (ARs), some of them are confined to mushroom structure which provides the shorted LH stub inductor through drilling via holes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of modern wireless communication systems, dual-band Doherty power amplifier [17] and dual-band-or dual-circularly polarized antenna and antenna array [18][19][20] featured lower cost and compact size have drawn much attention recently. Therefore, the branch-line couplers as the key components of it and several functions are required simultaneously, such as dualband operation, arbitrary coupling levels, and inherent impedance transforming.…”
Section: Introductionmentioning
confidence: 99%
“…They are used in lots of applications such as wireless local area network (WLAN), satellite communications and global system for mobile (GSM) [4]. In addition, different types of dual band microstrip patch antennas are presented in literatures such as dual band microstrip antenna with single patch [5] and stacked patches [6] and using two separate antennas which are connected to by a shorting pin [7] and using metamaterial branch-line coupler [8]. Chen et al [9] reported a modified inverted-L monopole with meandered wire and a conducting triangular.…”
Section: Introductionmentioning
confidence: 99%